The Limits of Sharenting: Exploring Parents’ and Adolescents’ Sharenting Boundaries Through the Lens of Communication Privacy Management Theory - Walrave, Michel; Verswijvel, Karen; Ouvrein, Gaëlle; Staes, Luna; Hallam, Lara; Hardies, Kris (Frontiers in Education, 2022)
Parents sharing information about their children on social network sites (i.e., sharenting) is a common practice today. However, previous work confronting parents’ and adolescents’ views on sharenting and related privacy concerns is limited. Therefore, the present study scrutinizes parents’ motives for sharenting as well as adolescents’ attitudes toward sharenting and negotiated privacy management strategies. Communication Privacy Management was used as a theoretical framework. Based on 30 semi-structured interviews, two motives for sharenting were identified. Parents share information of their adolescent children because they are proud of their offspring or to inform family and friends. Adolescents, on the other hand, approve parents’ sharenting behavior dependent on the content parents disclose online. Adolescents perceive sharenting as positive as long as they are nicely portrayed and positive events are shared. Additionally, both adolescents and parents are concerned about the child’s online privacy. They adopt several strategies to respect privacy boundaries and to avoid privacy turbulence.